Active microrheology with optical tweezers: a versatile tool to investigate anisotropies in intermediate filament networks. (29th December 2015) - Neckernuss, T; Mertens, L K; Martin, I; Paust, T; Beil, M; Marti, O
Abstract: Mechanical properties of cells are determined by the cytoskeleton and especially by intermediate filaments (IFs). To measure the contribution of IFs to the mechanics of the cytoskeleton, we determine the shear moduli of in vitro assembled IF networks consisting of keratin 8/18 and MgCl2, serving as a crosslinker. In this study we want to present a new method, a combination of active and passive microrheology, to characterize these networks. We also show the applicability of the new method and discuss new findings on the organization and force transmission in keratin networks gained by the new method. We trap and move embedded polystyrene particles with an optical tweezers setup in an oscillatory manner. The amplitude response of the trapped particle is measured and evaluated with a lock-in approach in order to suppress random motions. With this technique we determine the degree of isotropy of the assembled network and sense preferred directions due to inhomogeneities of the network. Furthermore, we show that we can deliberately create anisotropic networks by adjusting the assembly process and chamber geometry. To determine whether there are local network anisotropies in a globally isotropic network, we altered the evaluation method and included the motion of embedded particles in the vicinity of the trapped one. The correlations of the observed motions enable us to map local network anisotropies. Finally, we compare mechanical properties determined from passive with ones from active microrheology. We find the networks measured with the active technique to be approximately 20% more compliant than the ones from passive measurements.